To evaluate the hemoglobin concentration, lipid peroxidation and antioxidant status in patients with chronic kidney disease - V., Sheeba; P., Arun Kumar; P. K., Swarnalatha (International Journal of Research in Medical Sciences, 2016)
Background: Oxidative stress plays an important role in the progression of CKD as well as in many of the complications associated with the disease. ROS promotes inflammation, accelerated ageing, fibrosis and apoptosis leading to progression of CKD. Therefore, the present study was carried out to evaluate the serum markers for early diagnosis of patients at different stages of chronic kidney disease. Methods: The study group consisted of 50 patients with chronic kidney disease who were on conservative treatment with the age group of 20 to 60 years. Based on the creatinine clearance values the patients were assigned in to 3 groups; Stage 3, Stage- 4 and Stage- 5 as per NKF DOQI guidelines. Control group consisted of 50 age and sex matched, non-diabetic, nonsmoker healthy volunteers. About 5 ml of blood was collected and serum was used for the estimation of superoxide dismutase, ceruloplasmin and malondialdehyde and haemoglobin level using standard methods. The data was analyzed by applying student’s t test. The p value of ≤0.05 was taken as the level of significance. Results: The haemoglobin concentration in all the 3 CKD stages was found to be significantly decreased (p<0.000) whereas, the serum malondialdehyde (MDA) was significantly increased (p=0.000) in patients with CKD. But serum SOD and ceruloplasmin levels of normal and patients with CKD showed significant decline (p<0.000) only in stage 5 whereas, in stage-2 and stage-3 patients it did not show significant variation. Conclusions: The results of the study reinforce the possibility that antioxidant supplementation may be helpful in correcting anaemia in chronic kidney disease. Treatment of renal anaemia is an effective intervention to ensure better quality of life, to prevent adverse cardiovascular outcomes and to retard the progression of chronic kidney disease so as to reduce the burden of end stage renal disease in the long run.